Label‐free detection of invasive micropapillary carcinoma of the breast using multiphoton microscopy. Issue 3 (23rd October 2022) - He, Jiajia; Kang, Deyong; Shen, Tingfeng; Zheng, Liqin; Zhan, Zhenlin; Xi, Gangqin; Ren, Wenjiao; Chen, Zhong; Qiu, Lida; Xu, Shuoyu; Li, Lianhuang; Chen, Jianxin
Abstract: Invasive micropapillary carcinoma of the breast (IMPC) is a rare form of breast cancer with unique histological features, and is associated with high axillary lymph node metastasis and poor clinical prognosis. Thus, IMPC should be diagnosed in time to improve the treatment and management of patients. In this study, multiphoton microscopy (MPM) is used to label‐free visualize the morphological features of IMPC. Our results demonstrate that MPM images are well in agreement with hematoxylin and eosin staining and epithelial membrane antigen staining, indicating MPM is comparable to traditional histological analysis in identifying the tissue structure and cell morphology. Statistical analysis shows significant differences in the circumference and area of the glandular lumen and cancer nest between the different IMPC cell clusters with complete glandular lumen morphology, and also shows difference in collagen length, width, and orientation, indicating the invasive ability of different morphologies of IMPC may be different. Abstract : Invasive micropapillary carcinoma of the breast (IMPC) is a rare form of breast cancer with a poor outcome and should be diagnosed in time. In this study, multiphoton microscopy is used to label‐free visualize the morphological features of IMPC. And furthermore, it is found that the collagen features around the different kinds of IMPC cell clusters are different, indicating the different invasive ability of different morphologies of IMPC.